Ein Sara happy intersection design - Rajabi, Ishaq; Al-Zeer, Sara (جامعة بوليتكنك فلسطين - مساحة, 2015)
This project aims to study the traffic and geometry of ein sara happy bunny junction by making two or three alternatives to solve the traffic congestion. Traffic count, collision histories , signal timing and surveying shall be conducted , the collected field data and observations will be organized and analyzed by highway capacity manual 2010producer . different modeling tools will be used to analyze the exiting and proposed condition. The analysis leads to the development of possible design alternative that were evaluated in order to determine which would be recommended . Set of recommendations would be sent to Hebron municipality to be considered as future solution for this intersection , the model will reveal safety and effectiveness result.
no of pages 74, 28832, مساحة 3/2015 , in the store
Keywords: intersection designs